Penentuan Lokasi Pengisian Ulang Kendaraan Listrik untuk Distribusi Last Mile Menggunakan Set Covering Problem di Semarang - Zelania In Haryanto; Sayyidah Maulidatul Afraah (Pusat riset dan Inovasi Nasional, 2024)
The increasing use of electric vehicles in last-mile logistics distribution demands efficient and strategic charging infrastructure. This study aims to determine the optimal location for electric vehicle charging stations in Semarang City using the Set Covering Problem approach. A total of 17 last-mile distribution points operated by a logistics company were analyzed based on geographic data consisting of latitude and longitude coordinates, which were then processed into a distance matrix using the Euclidean formula. The optimization model was developed under the constraint of the electric vehicle’s maximum coverage radius and solved using binary linear programming. The analysis revealed that a single charging station located in Central Semarang is sufficient to cover all distribution points spread across the city. These findings reinforce the efficiency of the set covering approach in infrastructure planning and offer practical implications for logistics companies to optimize resources, minimize investment costs, and improve operational efficiency.